Bamboo as an Alternative Bioenergy Crop and Powerful Ally for Land Restoration in Indonesia - Sharma, R.; Wahono, J.; Baral, H. (MDPI, 2018)
The energy demand in Indonesia has increased significantly with its population growth, urbanization, and economic development. The growing concern of meeting energy demand while reducing dependency on fossil fuels has resulted in an increasing demand for renewable energy. As a country with a rich biomass base, bioenergy is now an important component of Indonesia’s energy agenda. However, a crucial problem in bioenergy production is the selection of species that can provide a sustainable supply of feedstock without having an impact on food security and the environment. In this context, we discuss the characteristics and benefits of using bamboo, a perennial grass, as a potential species for bioenergy feedstock in Indonesia. We describe the fuel characteristics of bamboo along with the possibility to align its cultivation, production, and usage with environmental and developmental agendas which makes it a suitable bioenergy crop in the country. In addition, its ability to grow on degraded lands, fast growth, long root system, and easy maintenance prove it as a powerful ally for the restoration of degraded land. We recommend in-depth research on the social, ecological, and economic feasibility of using this species for bioenergy production.